Basic technical mathematics - Washington, Allyn J. (The Benjamin/Cummings, 1978)
This tried-and-true text from Allyn Washington, the pioneer of the basic technical mathematics course, is intended for a two- or three-semester course and is taught primarily to students who plan to pursue technical fields. The primary strength of the text is the heavy integration of technical applications, which aids the student in pursuit of a technical career by showing the importance of a strong foundation in algebraic and trigonometric math.